Cobalt chloride-induced hepatic and intestinal damage in rats: protection by ethyl acetate and chloroform fractions of Ocimum gratissimum (2016)
Cobalt chloride is known to produce symptoms of diarrhea, vomiting and other gastrointestinal disturbances. We investigated the potential roles of the ethyl acetate and chloroform fractions of Ocimum gratissimum (OG), traditionally used to treat diarrhea and other gastrointestinal disorders in protection against cobalt chloride (CoCl2)-induced liver and intestinal damage. Wistar albino rats were given CoCl2 (350 ppm) in drinking water for 7 days, alone or concurrently with either fractions of OG at 100 and 200mg/kg each. Gallic acid (120 mg/kg) was administered to a group of rats as a standard flavonoid. Biochemical indices of oxidative stress, antioxidant enzyme activities, the levels of pro-inflammatory cytokines (Interleukin 1β; IL-1β and Tumor necrosis factor, TNF-α) were evaluated and the histological appearance of the liver and intestinal mucosa was investigated. CoCl2 produced significant elevations (p<0.05) in hydrogen peroxide (H2O2), malondialdehyde (MDA), IL-1β, alanine transaminase (ALT), aspartate transaminase (AST) and alkaline phosphatase (ALP). This was accompanied with significant reductions (p<0.05) in reduced glutathione (GSH), glutathione peroxidase (GPX) and glutathione S-transferase (GST) activities. Liver sections of rats exposed to CoCl2 had poor architecture and areas of necrosis with several dead hepatocytes, while some appeared with hyperchromic nuclei. Intestinal mucosa showed significant loss of absorptive epithelial cells with CoCl2 exposure. Treatment with the fractions from OG produced reduction in H2O2, MDA and IL-1β levels; reduced serum activities of ALT, AST and ALP; restoration of GSH levels and improved activities of GPX and GST. The fractions significantly preserved the hepatic and intestinal architecture.Our results indicate that the fractions of OG exhibited considerable hepatic and intestinal protection by reduction in levels of oxidants and pro-inflammatory cytokines, enhancement of antioxidant enzyme activities and preservation of tissue integrity and might thus be very useful agents in protecting the liver and intestines during concurrent exposure to Cobalt chloride.